2017
DOI: 10.1155/2017/9809702
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Characterization of Nanoengineered Fiber-Reinforced Composites: Effect of Carbon Nanotubes on the Out-of-Plane Mechanical Behavior

Abstract: The mechanical properties of the matrix and the fiber/matrix interface have a relevant influence over the mechanical properties of a composite. In this work, a glass fiber-reinforced composite is manufactured using a carbon nanotubes (CNTs) doped epoxy matrix. The influence of the CNTs on the material mechanical behavior is evaluated on the resin, on the fiber/matrix interface, and on the composite. On resin, the incorporation of CNTs increased the hardness by 6% and decreased the fracture toughness by 17%. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The first phenomenon consists of areas of CNTs with a good interface between the fibers and resin (Fig. 7f), where the adherence of CNTs is good with respect to both the fibers and resin [46][47][48][49] . However, the second phenomenon appears in areas, such as those shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first phenomenon consists of areas of CNTs with a good interface between the fibers and resin (Fig. 7f), where the adherence of CNTs is good with respect to both the fibers and resin [46][47][48][49] . However, the second phenomenon appears in areas, such as those shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the out-of-plane mechanical resistance of composite materials, the properties of both the matrix and fiber-matrix interface should be improved. Several authors [23][24][25][26][27] considered adding carbon nanoparticles to composite materials and concluded that this approach improves the properties of the fiber-matrix interface and toughness of the matrix. For instance, Boroujeni and Al-Haik 28 obtained a 20% and 50% increase in tensile strength and fatigue life of a carbon FRC with carbon nanotubes (CNTs) compared with the original material.…”
Section: Introductionmentioning
confidence: 99%
“…Gonzales and Llorca 16 show that the increase in IFSS directly influences the transverse compressive strength. Medina et al 24 incorporated a masterbatch of MWCNTs in a glass FRC and improved the IFSS by 24%. Later, Bedi et al, 37 found an increase of the IFSS by grafting CNTs onto the surface of carbon fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Phomrak and Phisalaphong [18] attempted with bacterial cellulose (BC) to reinforce the NR latex and concluded that the tensile strength was increased 94% higher than pure NR latex. Medina et al [19] prepared a glass fiber reinforced composite using CNTs doped epoxy and concluded that incorporation of CNTs increased the hardness by 6% and decreased the fracture toughness by 17%.…”
Section: Introductionmentioning
confidence: 99%